Effective Use of Percutaneous Stellate Ganglion Blockade in Patients With Electrical Storm. (September 2019) - Tian, Ying; Wittwer, Erica D.; Kapa, Suraj; McLeod, Christopher J.; Xiao, Peilin; Noseworthy, Peter A.; Mulpuru, Siva K.; Deshmukh, Abhishek J.; Lee, Hon-Chi; Ackerman, Michael J.; Asirvatham, Samuel J.; Munger, Thomas M.; et al.
Abstract : Background: Percutaneous stellate ganglion blockade (SGB) has been used for drug-refractory electrical storm due to ventricular arrhythmia (VA); however, the effects and long-term outcomes have not been well studied. Methods: This study included 30 consecutive patients who had drug-refractory electrical storm and underwent percutaneous SGB between October 1, 2013, and March 31, 2018. Bupivacaine, alone or combined with lidocaine, was injected into the neck with good local anesthetic spread in the vicinity of the left stellate ganglion (n=15) or both stellate ganglia (n=15). Data were collected for patient clinical characteristics, immediate and long-term outcomes, and procedure-related complications. Results: Clinical characteristics included age, 58±14 years; men, 73.3%; and left ventricular ejection fraction, 34±16%. At 24 hours, 60% of patients were free of VA. Patients whose VA was controlled had a lower hospital mortality rate than patients whose VA continued (5.6% versus 50.0%; P =0.009). Implantable cardioverter-defibrillator interrogation showed a significant 92% reduction in VA episodes from 26±41 to 2±4 in the 72 hours after SGB ( P <0.001). Patients who died during the same hospitalization (n=7) were more likely to have ischemic cardiomyopathy (100% versus 43.5%; P =0.03) and recurrent VA within 24 hours (85.7% versus 26.1%; P =0.009). There were no procedure-related major complications. Conclusions: SGB effectively attenuated electrical storm in more than half of patients without procedure-related complications. Percutaneous SGB may be considered for stabilizing ventricular rhythm in patients for whom other therapies have failed.